2021
DOI: 10.1021/jacs.1c08157
|View full text |Cite
|
Sign up to set email alerts
|

Late-Stage N-Me Selective Arylation of Trialkylamines Enabled by Ni/Photoredox Dual Catalysis

Abstract: The diversity and wide availability of trialkylamines render them ideal sources for rapid construction of complex amine architectures. Herein, we report that a nickel/photoredox dual catalysis strategy affects site-selective α-arylation of various trialkylamines. Our catalytic system shows exclusive N-Me selectivity with a wide range of trialkylamines under mild conditions, even in the context of late-stage arylation of pharmaceutical compounds bearing this common structural motif. Mechanistic studies indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…of (2,2,6,6-tetramethylpiperidin-1-yl)­oxyl (TEMPO), indicating a possible radical pathway. Moreover, a diamine product was detected by high-resolution mass spectrometry (HRMS), which was probably formed by the radical addition of an α-amino radical to an iminium ion intermediate . Furthermore, silyl ketene acetal 68 was synthesized and subjected into the standard conditions (Scheme e).…”
mentioning
confidence: 99%
“…of (2,2,6,6-tetramethylpiperidin-1-yl)­oxyl (TEMPO), indicating a possible radical pathway. Moreover, a diamine product was detected by high-resolution mass spectrometry (HRMS), which was probably formed by the radical addition of an α-amino radical to an iminium ion intermediate . Furthermore, silyl ketene acetal 68 was synthesized and subjected into the standard conditions (Scheme e).…”
mentioning
confidence: 99%
“…The reaction also proceeded with other electron donors; while N , N ‐diisopropylethylamine (DIPEA) afforded a clean transformation (entry 11), pentamethylpiperidine (PMP) gave a low yield of the desired product (entry 12). No aryl‐amino alkyl coupling product was formed despite the commonly observed reactivity of α‐amino radicals in dual Ni/photoredox catalysis, [15] implying that the XAT process predominates over other pathways like interception of such radicals by Ni II/I [15b,c] . Recent studies have shown that the radical anions of 4‐CzIPN and its derivatives can be photoexcited to afford potent reductants that can reduce substrates with redox potentials more negative than −2.0 V [16] .…”
Section: Resultsmentioning
confidence: 99%
“…[33] In 2021, Shen and Rovis published a late-stage functionalization protocol for the N-methyl arylation of trialkylamines enabled by dual Ni/organophotoredox catalysis (Figure 9). [65] The authors envisaged the use of 4-CzIPN (17) as organic dye together with a Ni II metal complex 5 e to achieve the selective production of pharmaceutically relevant derivatives under blue light irradiation. A variety of aryl bromides 2 b were effectively coupled with different amines 6 to generate the corresponding benzylamines 24 under mild reaction conditions (up to 91 % yield).…”
Section: Dual Ni/organophotoredox Catalysismentioning
confidence: 99%